Innovative Model of Practice-Oriented Training of Employees of the Town-Forming Enterprise in the Mining Region (by the Example of JSC “SUEK-Kuzbass”) - Kulay Svetlana; Kayachev Gennady (E3S Web of Conferences, 2017)
The article proposes to improve the system of training of employees of joint-stock company SUEK-Kuzbass in the educational institutions of the Kemerovo region according to the requirements of the company using practice-oriented training technology. The aim of the work is to substantiate the effectiveness of implementing practice-oriented training, identify priority directions and ways of its development. The main objectives of the study are: to identify the main advantages for the company and students; determine the criteria for the success and practical value of applying practice-oriented training for the company; conduct a comparative analysis of the target and practice-oriented model of training for the company. The real needs of the employer through the dual form of training were taking into account. The expansion of positive experience in training engineering personnel in higher education in technology-based training with the involvement of specialists from other regions of the company and expanding training in mining was also included.